ʼOd gsal sñiṅ poʼi mkhregs gcod kyi khrid gser gyi them skas : an explanation of the khregs-chod aspect of profound Rdzogs-chen practice - ʼJigs-med-dpaʼ-bo (Sherab Gyaltsen Lama, 1976)
Explanation of an aspect of Dzogchen practice of the Nyingmapa tradition.